SIMULASI SISTEM HIBRID PHOTOVOLTAIC-PLN-BATERAI PADA KINCIR AIR TAMBAK UDANG BERBASIS PLC - Rachmad Ikhsan; Safwan (J-Innovation, 2020)
At this time to turn on the waterwheel on shrimp ponds, electricity sources from PLN are used or often also use generatorsas a backup power source. So to overcome this problem, a hybrid system with an energy source from Photovoltaic (PV) -PLN-Batteries with voltage output is used to drive a waterwheel in a shrimp pond. The purpose of this study is to reducethe use of electrical energy from PLN and also generators with fuel oil which will gradually run out of energy sources. Themethod used includes PV with a power of 200Wp and an output voltage of 12V, the energy generated by the PV is receivedby the solar charge control which is stored in a 3000 mAh capacity battery. The output voltage generated from PV isdetected by the ZMPT sensor 101B (voltage sensor) which will provide input data to the PLC to be processed with amaximum voltage of 25VDC, when the battery voltage is empty, the PLC will change the input of electrical energy that wasoriginally supplied from the battery into an electrical energy input from PLN sources. The results of the system simulationare obtained that every condition that is tried can be run in accordance with expectations, namely the voltage sensor candetect each voltage signal from the three voltage inputs originating from PV, PLN and also the battery.